1995
DOI: 10.1111/j.1525-1594.1995.tb02318.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrotactile Stimulator for Artificial Proprioception

Abstract: With the goal of investigating artificial proprioception elicited by electrical stimulation, we have developed a tactile phi phenomenon-based stimulator. This two-channel microprocessed pulse amplitude modulation system generates two different envelope waveforms (triangular and elliptical) and allows programming and visualizing of its main parameters: pulse with (0.1-10 ms), pulse frequency (0.1-10 kHz), modulation frequency (0.3-10 Hz), current intensity (up to 20 mA), and the amplitude modulation index (0-10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
6

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 20 publications
0
10
0
6
Order By: Relevance
“…This method consists of evoking a moving fused image through 3 pairs of electrodes close to each other when the amplitude of the stimulating signal varies temporarily and complementarily. Preliminary experiments (29) showed that the best results were obtained with square pulses of 100 Hz, 1 Hz for modulation frequency, and an elliptical envelope waveform (Fig. 1).…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…This method consists of evoking a moving fused image through 3 pairs of electrodes close to each other when the amplitude of the stimulating signal varies temporarily and complementarily. Preliminary experiments (29) showed that the best results were obtained with square pulses of 100 Hz, 1 Hz for modulation frequency, and an elliptical envelope waveform (Fig. 1).…”
Section: Methodsmentioning
confidence: 95%
“…A stimulator based on a tactile phi phenomenon (29,30) was used for artificial proprioception. This method consists of evoking a moving fused image through 3 pairs of electrodes close to each other when the amplitude of the stimulating signal varies temporarily and complementarily.…”
Section: Methodsmentioning
confidence: 99%
“…When the fingertip was in contact with the trigger, the displacement of the trigger from its resting position and its spring constant determined the contact force between the trigger and the fingertip. The simulated finger contact force was applied to and resisted the finger's simulated motion and can be used to drive haptic feedback devices such as electrotactile or vibrotactile stimulators placed on the skin of the residual limb (K. Kim, Colgate, Santos-Munne, Makhlin, & Peshkin, 2010;Nohama, Lopes, & Cliquet, 1995). Such haptic feedback enables the patient to feel and therefore regulate the level of finger contact force more effectively.…”
Section: Simulation Of Collision Andmentioning
confidence: 99%
“…In addition, such sensory substitution techniques can also be used to provide the human with feedback about the advanced robotic perception of the environment (e.g., depth sensors [Plagemann et al, 2010]), that may not be covered by the human sensory system. Examples include vibrotactile, electrocutaneous or mechanical pressure [Shannon, 1976, Nohama et al, 1995, Wang et al, 1995, to convey information about force, proprioception, and/or texture. By the same token, previous works recognized different types of non-invasive sensory substitution techniques, roughly dividing haptic information into low-frequency, e.g.…”
Section: Interfaces For Improved Human Perceptionmentioning
confidence: 99%